Individual Roles and Approaches to Public Engagement in a Community-University Partnership in a Rural California Town - Esther Prins (Journal of Research in Rural Education, 2006)
This case study examines the roles that a professor, graduate student, consultant, and community education specialist at a public university in California have played in a partnership with an elementary school and a community-based organization in a nearby rural town. The case reveals that individuals' roles and approaches to public engagement evolve over time and differ markedly. Moreover, the actions of university personnel espousing community-driven partnerships may unconsciously reflect hierarchical power relations. The article discusses implications for community-university partnerships, especially in rural areas. University personnel should decide who is responsible for taking initiative in establishing the partnership and setting the partnership agenda, consider how to exercise power in supportive and directive ways, and coordinate their activities. Coordination among personnel and academic departments is especially important in rural communities, where school staff and community leaders and residents may become overwhelmed with multiple requests to participate in projects and research.